Perceptions of love and sex across the adult life span - Felix Neto (2012)
Four distinct aspects of the perceptions of love and sex have recently been proposed: (a) Love is Most Important - the emotion of love is more important than anything else; (b) Sex Demonstrates Love - although sex is important, it demonstrates the deeper sentiment of love; (c) Love Comes Before Sex - love comes before and "drives" sex; and (d) Sex is Declining - sex diminishes in a relationship (Hendrick & Hendrick, 2002). This study explored the factor structure of perceptions of love and sex in a Portuguese sample throughout the adult life span. A total of 924 men and women (52% women) participated, all of whom were currently in a romantic relationship. The Perceptions of Love and Sex Scale showed the same four-factor structure that was evidenced in U. S. samples, and acceptable psychometric properties. Age and gender influenced these perceptions of love and sex. Expected correlations with measures of other relationship constructs were found.